The Lived Experience of Patients and Family Caregivers in Managing Pneumoconiosis. (July 2021) - Li, Polly W. C.; Yu, Doris S. F.; Tam, Samuel Y. S.
The daily challenges of patients with pneumoconiosis and their caregivers in living with and providing care for this disease remain unexplored. As guided by the interpretive description, we found that pneumoconiosis patients suffered from highly anxiety-provoking symptoms and physical debilitation, which evoked high levels of distress and sense of impending death. The reduced functional capacity disrupted patients' role functioning and self-esteem. The perceived stigma of the embarrassing symptoms and treatments further disrupted their self-concept and social lives. Providing care for pneumoconiosis patients was demanding and burdensome, which jeopardized family caregivers' physical, emotional, and social well-being, and the relationship strain with the patients added further frustration to them. The perceived caregiving gain supported them to fully engage in daily caregiving. To improve the well-being of pneumoconiosis patients, a comprehensive empowerment-based dyadic care model is required to optimize adaptive behavioral changes and self-esteem, and improve self-efficacy in disease management for this cohort.